Penilaian Mata Pelajaran Bahasa Inggris - Mutiara O Panjaitan (Jurnal Pendidikan dan Kebudayaan, 2010)
The learning process of English subject is designed in line with the way English is used in society in everyday life. Teaching learning activity and assessment are integrated process. It means that assessment executed while learning activity is going on. Based on the investigation on school curriculum it is that learning activity and assessment were designed as separate components and in formal way. The task of assessment does not depict the real word. Besides, teachers’ ability in designing assessment is various that will influence quality of output. Based on this situation it is needed to develop a model of assessment on English subject that could be used as a reference for teacher and stakeholders when developing school curriculum. Language is a tool for communication orally and written. Communication competence or discourse competence is a competence to communicate orally and written as well in certain communication event. Communicative competence needs a set of competencies i.e. actional competence, linguistic competence, discourse competence, sociocultural competence, and strategic competence. These competencies could not be separated and support each other which are realized through four language skills, i.e. listening, speaking, reading, and writing.Teachers are encourage to teach language using the four language skills in an integrated manner.